Mutations in cdsA and pgsA Correlate with Daptomycin Resistance in Streptococcus mitis and S. Oralis (2019)
We investigated the ability of several recent clinical viridans group streptococci (VGS) bloodstream isolates (Streptococcus mitis/S. oralis subgroup) from daptomycin (DAP)-naive patients to develop DAP resistance in vitro. All strains rapidly developed high-level and stable DAP resistance. Substitutions in two enzymes involved in the cardiolipin biosynthesis pathway were identified, i.e., CdsA (phosphatidate cytidylyltransferase) and PgsA (CDP-diacylglycerol-glycerol-3-phosphate-3phosphatidyltransferase). These mutations were associated with complete disappearance of phosphatidylglycerol and cardiolipin from cell membranes. DAP interactions with the cell membrane differed in isolates with PgsA versus CdsA substitutions